Design and Development of an All-Terrain Vehicle with Magnetic Heading for Enhanced Precision (International Journal of Communication Systems and Network Technologies, 2020)
This research paper presents the design and development of an innovative All-Terrain Vehicle (ATV) equipped with magnetic heading technology to achieve enhanced precision in navigation. The vehicle is tailored for operation in challenging terrains where traditional navigation systems may face limitations. The integration of magnetic heading technology allows for improved accuracy in determining the vehicle's direction, particularly in environments where GPS signals are unreliable or unavailable.The paper discusses the conceptualization and design phases, highlighting the incorporation of magnetic sensors and advanced control systems to enable precise heading measurements. Additionally, the implementation of a robust and adaptable chassis, suspension, and propulsion system is explored to ensure the ATV's capability to traverse diverse terrains effectively.Through systematic testing and validation, the paper demonstrates the effectiveness of the proposed ATV in achieving enhanced precision during navigation. The magnetic heading technology is evaluated in various challenging scenarios, showcasing its potential to overcome common limitations associated with traditional navigation methods.The outcomes of this research contribute to the advancement of all-terrain vehicle technology, particularly in contexts where precise navigation is critical. The proposed design and integration of magnetic heading technology offer a promising solution for applications such as agricultural field operations, search and rescue missions, and exploration in remote or GPS-denied areas.
Keywords: All-Terrain Vehicle (ATV); Magnetic Heading; Precision Navigation; Challenging Terrain; Navigation Technology; Control Systems; Sensor Integration; GPS-denied Environments; Robust Chassis; Suspension System; Propulsion System; Field Operations; Search and Rescue; Exploration; Vehicle Design; Enhanced Precision; Magnetic Sensors; Terrain Adaptability; Navigation Accuracy; Validation Testing